Development of Innovative Comprehensive Hospitality Program for Improving International Ukrainian-French Relations - Саркісян, Ганна Овсепівна; Тітомир, Людмила Анатоліївна (Київський національний університет імені Тараса Шевченка, 2019)
The aim of the work is to find ways to improve the Ukrainian-French socio-economic relations, to organize a program of hospitality for the stay of French students in Ukraine. Methodology. The object of analysis, generalizations and research is the development of measures for the development of economic relations between the countries under study through the organization of gastronomic, wine, business, scientific and cognitive, complex tours.The objective of the work is to identify the objects for cooperation, to develop a model of cooperation. Results. Based on the results of the work, a draft project for a visit to French students for the national-language curriculum has been developed, and animation, cultural and entertainment events have been proposed to promote French culture among Ukrainian youth and further cultural exchange among the countries under study. Scientific novelty. Models of cooperation have been developed by organizing gastronomic, wine, business, scientific and educational, comprehensive tours. Practical significance. The results can be used in the hospitality industry to expand additional services.

Метою роботи є пошук шляхів покращення україно-французьких соціально економічних відносин, організація програми гостинності для перебування французських студентів на Україні. Методика. Об'єктом аналізу, узагальнень і дослідження виступає розробка заходів для розвитку економічних відносин між досліджуваними країнами через організацію гастрономічних, винний, ділових, науково- пізнавальних, комплекних турів. Результати. За результатами виконаної роботи розроблено проект візиту для французьких студентів на навчальний модуль з урахуванням національних вподобань та запропоновано анімаційні, культурно-розважальні заходи для популяризації французської культури серед української молоді і подальшого культурного обміну між досліджуваними країнами. Наукова новизна. Розроблено моделі співпраці через організацію гастрономічних, винний, ділових, науково- пізнавальних, комплекних турів. Практична значимість. Одержані результати можуть бути використані в індустрії гостинності для розширення додаткових послуг.
Розробка інноваційної комплексної програми гостинності для покращення міжнародних україно-французьких відносин
Keywords: гостинність; готельний бізнес; винні та гастрономічні тури; інновації; міжнародні відносини; анімаційні програми; hospitality; hotel business; wine and gastronomic tours; innovations; international relations; animation prog